Early Start DENVER Model: A Meta - analysis - Jane P. Canoy; Helen B. Boholano (Intelektual Pustaka Media Utama, 2015)
Each child with Autism Spectrum Disorder has different symptoms, skills and types of impairment or disorder with other children. This is why the word “spectrum” is included in this disorder. Eapen, Crncec, and Walter, 2013 claimed that there was an emerging evidence that early interventions gives the greatest capacity of child’s development during their first years of life as “brain plasticity” are high during this period. With this, the only intervention program model for children as young as 18 months that has been validated in a randomized clinical trial is “Early Start Denver Model” (ESDM). This study aimed to determine the effectiveness of the outcome of “Early Start Denver Model” (ESDM) towards young children with Autism Spectrum Disorders. This study made use of meta-analysis method. In this study, the researcher utilized studies related to “Early Start Denver Model (ESDM)” which is published in a refereed journal which are all available online. There were five studies included which totals 149 children exposed to ESDM. To examine the “pooled effects” of ESDM in a variety of outcomes, a meta-analytic procedure was performed after the extraction of data of the concrete outcomes. Comprehensive Meta Analysis Version 3.3.070 was used to analyze the data. The effectiveness of the outcome of “Early Start Denver Model” towards young children with Autism Spectrum Disorders (ASD) highly depends on the intensity of intervention and the younger child age. This study would provide the basis in effectively implementing an early intervention to children with autism such as the “Early Start Denver Model” (ESDM) that would show great outcome effects to those children that has “Autism Spectrum Disorder”.